The Koran - Dawood, N. J. [Translator; Writer of added commentary] (London Penguin Books, 1990)
The Koran, as N.J. Dawood states, is 'not only one of the most influential books of prophetic literature but also a literary masterpiece in its own right'. Universally accepted by Muslims to be the infallible Word of God as revealed to Mohammed by the Angel Gabriel nearly fourteen hundred years ago, the Koran still provides the rules of conduct fundamental to the Arab way of life. N.J. Dawood's masterly translation, first published in the mid-1950s and now completely revised in the light of a life-long study of the language and style of the Koran, presents the English reader with a clear, fluent and authoritative rendering, while fully reflecting the characteristic flavour and rhythm of the original. The present edition follows the original sequence of the Koranic suras, and is provided with a comprehensive index.
Keywords: Qurʼan stories. Koran. Islam